Pathologic responses and surgical outcomes after neoadjuvant immunochemotherapy versus neoadjuvant chemoradiotherapy in patients with locally advanced esophageal squamous cell carcinoma - Xu, Lei; Wei, Xiu-feng; Li, Can-jun; Yang, Zhao-yang; Yu, Yong-kui; Li, Hao-miao; Xie, Hou-nai; Yang, Ya-fan; Jing, Wei-wei; Wang, Zhen; Kang, Xiao-zheng; Zhang, Rui-xiang; et al. (Frontiers in Immunology, 2022)
Background: Currently, the role of immunotherapy in neoadjuvant setting for patients with locally advanced esophageal squamous cell carcinoma (ESCC) is gradually attracting attention. Few studies compared the efficacy of neoadjuvant immunochemotherapy (NICT) and neoadjuvant chemoradiotherapy (NCRT). Our study aimed to compare treatment response and postoperative complications after NICT followed by surgery with that after conventional NCRT in patients with locally advanced ESCC. Methods: Of 468 patients with locally advanced ESCC, 154 received conventional NCRT, whereas 314 received NICT. Treatment response, postoperative complications and mortality between two groups were compared. Pathological response of primary tumor was evaluated using the Mandard tumor regression grade (TRG) scoring system. Pathological complete response (pCR) of metastatic lymph nodes (LNs) was defined as no viable tumor cell within all resected metastatic LNs. According to regression directionality, tumor regression pattern was summarized into four categories: type I, regression toward the lumen; type II, regression toward the invasive front; type III, concentric regression; and type IV, scattered regression. Inverse probability propensity score weighting was performed to minimize the influence of confounding factors. Results: After adjusting for baseline characteristics, the R0 resection rates (90.9% vs. 89.0%, P=0.302) and pCR (ypT0N0) rates (29.8% vs. 34.0%, P=0.167) were comparable between two groups. Patients receiving NCRT showed lower TRG score (P<0.001) and higher major pathological response (MPR) rate (64.7% vs. 53.6%, P=0.001) compared to those receiving NICT. However, NICT brought a higher pCR rate of metastatic LNs than conventional NCRT (53.9% vs. 37.1%, P<0.001). The rates of type I/II/III/IV regression patterns were 44.6%, 6.8%, 11.4% and 37.1% in the NICT group, 16.9%, 8.2%, 18.3% and 56.6% in the NCRT group, indicating a significant difference (P<0.001). Moreover, there were no significant differences in the incidence of total postoperative complications (35.8% vs. 39.9%, P=0.189) and 30-d mortality (0.0% vs. 1.1%, P=0.062). Conclusion: For patients with locally advanced ESCC, NICT showed a R0 resection rate and pCR (ypT0N0) rate comparable to conventional NCRT, without increased incidence of postoperative complications and mortality. Notablely, NICT followed by surgery might bring a promising treatment response of metastatic LNs.